Coronavirus disease 2019 (COVID-19) vaccine acceptability in Ghana: An urban-based population study - Hannah Benedicta Taylor-Abdulai; Edem Kojo Dzantor; Nathan Kumasenu Mensah; Mubarick Nungbaso Asumah; Stephen Ocansey; Samuel Kofi Arhin; Precious Barnes; Victor Obiri Opoku; Zakariah Jirimah Mankir; Sylvester Ackah Famieh; Collins Paa Kwesi Botchey (PLoS ONE, 2025)
Introduction Coronavirus disease 2019 (COVID-19) vaccine hesitancy is a complex health challenge characterized by a delay in the acceptance or refusal of the vaccination with context-specific determinants. Our study, therefore, assessed the COVID-19 vaccine acceptance among urban dwellers in the Central Region, of Ghana. Methods A cross sectional study was conducted between September and November, 2022 using a multi-stage cluster sampling procedure among 377 participants. A modified World Health Organization pretested paper-based questionnaire was administered to study participants. The data was analyzed using Statistical Package for Social Sciences (SPSS) version 26. Descriptive and inferential statistics were carried out and results were summarized into frequencies, percentages, tables, and charts for clarity. A conventional p-value < 0.05 was considered statistically significant. Results The study revealed that COVID-19 vaccine acceptance was 20.0% (76/377) and vaccine hesitancy was 80.0% (301/377). Out of the 377 participants, their socio-demographic characteristics showed that the majority were below 25 years 53.8% (203/377), [vaccine acceptance; 36.84% (28/76) vs vaccine hesitancy; 58.14% (175/301)], and females 50.1% (189/377), [vaccine acceptance; 56.58% (43/76) vs vaccine hesitancy; 48.50% (146/301)]. Common reasons for COVID-19 vaccine hesitancy included mistrust of the source of the vaccine, personal belief and experience, mistrust of the drug development process, mistrust in the health system, and mistrust of the pharmaceutical company. Age above 25 years, female, educational levels, senior high school and above, being employed, and hearing of new vaccine had a significance influence on COVID-19 vaccine acceptance. Conclusion COVID-19 vaccine acceptance was low with high vaccine hesitancy among participants. The study’s findings highlights the importance of addressing vaccine hesitancy through building trust in the vaccine development processes, including the provision of accurate information about the vaccine safety and efficacy. Resolving concerns related to the source of the vaccine and the overall healthcare system are important to address vaccine hesitancy. Policy makers could adopt tailored interventions targeting specific demographic groups, such as the younger population and females to increase vaccine acceptance. Ghana’s public health authorities could adopt the findings to re-strategize its urban COVID-19 vaccine campaigns to address misconceptions and misinformation to increase vaccine acceptance.